Status quo and influencing factors of readiness for hospital discharge in patients with brain tumours after surgery - Qin, Yue-Hong (Frontiers in Oncology, 2024)
ObjectiveThis study aimed to investigate the status quo of readiness for hospital discharge in patients with brain tumours after surgery and to analyse its influencing factors.MethodA total of 300 patients with brain tumours who were admitted to the neurosurgery ward of our hospital between September 2020 and December 2022 were selected as the study participants using the convenient sampling method. The readiness for hospital discharge in patients with brain tumours after surgery was investigated using a general information questionnaire, the Readiness for Hospital Discharge Scale (RHDS), the Quality of Discharge Teaching Scale (QDTS), the University of Washington Quality of Life Questionnaire (UW-QOL), and the Social Support Rating Scale (SSRS), and its influencing factors were analysed.ResultsThe total RHDS score of patients with brain tumours was (155.02 ± 14.67), which was at a medium level. There was a positive correlation between readiness for hospital discharge in patients with brain tumours after surgery and the UW-QOL score (r = 0.459, p = 0.001), SSRS score (r = 0.322, p = 0.000), and QDTS score (r = 0.407, p = 0.001). The influencing factors of readiness for hospital discharge in patients with brain tumours included the content actually obtained by patients (health guidance) before discharge (p = 0.001), discharge teaching skills (p = 0.001), age (p = 0.006), swallowing status (p = 0.021), education level (p = 0.016), and objective support (p = 0.022).ConclusionThe readiness for hospital discharge in patients with brain tumours is at a medium level. Medical staff should give inpatients more targeted knowledge and implement personalised health education according to the patient’s age, education level, swallowing status, and objective support to improve the patient’s readiness for hospital discharge.